Notes - Mathematics Olympiads - Limits and Derivatives
Category : 11th Class
Limits and Derivatives
Key Points to Remember
A number, (\[\ell \] is said to be the limit of the function \[\text{y=f}(x)\] at\[x=a\], then \[\exists \] a positive number, \[\in \,\,>\,\,0\] corresponding to the small positive number \[\delta \,>\,\,0\] such that
\[\left| \text{f(x)-}\left. \ell \right| \right.\,<\,\varepsilon ,\] provided \[\left| x-\left. a \right| \right.\,<\,\delta \]
Evidently,
\[\underset{x\to \,a}{\mathop{\lim }}\,\,\,f(x)=\ell \]
We have to learn how to evaluate the limit of the function \[y=f(x)\]
Only three type of function can be evaluate the limit of the function.
Now, basically, there are three method to evaluate the limit of the function.
i.e. \[\underset{x\to a}{\mathop{\lim }}\,\frac{{{x}^{n}}-{{a}^{n}}}{x-a}=n.{{a}^{n-1}}\]
\[={{3.3}^{2}}=27\]
Dividing numerator and denomiator by (x -1), when
\[=\underset{x\to 1}{\mathop{\lim }}\,\frac{{{x}^{15}}-{{1}^{15}}}{\frac{x-1}{\frac{{{x}^{^{10}}}-{{(1)}^{10}}}{x-1}}}=\frac{15.{{(1)}^{15-1}}}{10.{{(1)}^{10-1}}}=\frac{15}{10}=\frac{3}{2}\]
\[=\underset{x\to 0}{\mathop{\lim }}\,\frac{1+x-1}{x(\sqrt{1+x+1)}}[\therefore \,\,{{a}^{2}}-{{b}^{2}}=(a+b)(a-b)]=\underset{x\to 0}{\mathop{\lim }}\,\frac{1}{(\sqrt{1+x+1)}};\]
applying limit, \[x\to 0\],we have \[=\frac{1}{1+1}=\frac{1}{2}\]
\[\underset{x\to 2}{\mathop{\lim }}\,\frac{(x+2)(x-2)}{x-2}=2+2=4\]
Q, \[\underset{\mathbf{x3}}{\mathop{\mathbf{lim}}}\,\frac{{{\mathbf{x}}^{\mathbf{4}}}\mathbf{-81}}{\mathbf{2}{{\mathbf{x}}^{\mathbf{2}}}\mathbf{-5x-3}}\mathbf{=}\underset{\mathbf{x3}}{\mathop{\mathbf{lim}}}\,\frac{{{\mathbf{x}}^{\mathbf{4}}}\mathbf{-(3}{{\mathbf{)}}^{\mathbf{4}}}}{\mathbf{2}{{\mathbf{x}}^{\mathbf{2}}}\mathbf{-6x+x-3}}\]
\[\underset{x\to 3}{\mathop{\lim }}\,\frac{{{({{x}^{2}})}^{2}}-{{({{3}^{2}})}^{2}}}{2x(x-3)+1(x-3)}=\underset{x\to 3}{\mathop{\lim }}\,\frac{({{x}^{2}}-9)-({{x}^{2}}+9)}{(x-3)(2x+1)}=\underset{x\to 3}{\mathop{\lim }}\,\frac{(x+3)(x-3)({{x}^{2}}+9)}{(x-3)(2x+1)}\]
Applying limit as \[x\to 3\], we have
\[=\frac{(3+3)({{3}^{2}}+9)}{(2\times 3+1)}=\frac{6\times 18}{7}=\frac{108}{7}\]
If \[\underset{x\to a}{\mathop{\lim }}\,\,\,\text{f(x)=}\ell \]and \[\underset{x\to a}{\mathop{\lim }}\,\,\,g\text{(x)=m}\] then the following results are true:
(a) \[\underset{x\to a}{\mathop{\lim }}\,\,\left[ f(x)\pm \,g\text{(x)} \right]\text{=}\underset{x\to a}{\mathop{\lim }}\,\,\,\text{f(x)}\pm \underset{x\to a}{\mathop{\lim }}\,\,\,g(x)=\ell +m\]
(b) \[\underset{x\to a}{\mathop{\lim }}\,\,\left\{ k.\text{f(x)} \right\}\text{=k}\text{.}\,\underset{x\to a}{\mathop{\lim }}\,\,\,\text{f(x)}\text{.}\,=k.\ell .\]
(c) \[\underset{x\to a}{\mathop{\lim }}\,\,\left\{ k.\text{f(x)} \right\}\text{=k}\text{.}\,\underset{x\to a}{\mathop{\lim }}\,\,\,\text{f(x)}\text{.}\,\underset{x\to a}{\mathop{\lim }}\,\,\,g(x)=\ell +m.\]
(d) \[\underset{x\to a}{\mathop{\lim }}\,\,\left\{ \frac{\text{f(x)}}{g(x)} \right\}\text{=}\frac{\underset{x\to a}{\mathop{\lim }}\,\,\,\text{f(x)}}{\underset{x\to a}{\mathop{\lim }}\,\,\,g\text{(x)}}=\frac{\ell }{m}[i\text{f}\,\,\text{m}\ne \text{0 }\!\!]\!\!\text{ }\]
(e) \[\underset{x\to a}{\mathop{\lim }}\,\,\text{f(x)=+}\infty \]or\[\text{-}\,\infty \], then \[\underset{x\to a}{\mathop{\lim }}\,\,\frac{1}{\text{f(x)}}\text{=0}\]
(f) \[\underset{x\to a}{\mathop{\lim }}\,\,\,\log \left\{ g(x) \right\}\,=\log \left[ \underset{x\to a}{\mathop{\lim \,g(x)}}\, \right]=\log \,m,\,m>0\frac{1}{\text{f(x)}}\text{=0}\]
(g) \[\underset{x\to a}{\mathop{\lim }}\,\,\,{{\left[ f(x) \right]}^{g(x)}}\,={{\{\underset{x\to a}{\mathop{\lim }}\,\,\text{f(x) }\!\!\}\!\!\text{ }}^{\underset{x\to a}{\mathop{\lim \,\,\,g(x)}}\,}}={{\ell }^{m}}\]
10. \[{{e}^{x}}=1+x+\frac{{{x}^{2}}}{2}+\frac{{{x}^{3}}}{3}+\frac{{{x}^{4}}}{4}+.....to\infty \]
11. \[{{e}^{-x}}=1-x+\frac{{{x}^{2}}}{2}-\frac{{{x}^{3}}}{3}+\frac{{{x}^{4}}}{4}-.....to\infty \]
13. \[{{a}^{x}}=1+x\log a+\frac{{{(x\log a)}^{2}}}{2}+.....to\infty \]
15. \[\cos x=1-\frac{{{x}^{2}}}{2}+\frac{{{x}^{4}}}{4}-\frac{{{x}^{6}}}{6}+......to\infty \]
16. \[\tan x=x-\frac{{{x}^{3}}}{3}+\frac{{{x}^{5}}}{5}+.....to\infty \]
17. \[{{\tan }^{-1}}x=x-\frac{{{x}^{3}}}{3}+\frac{{{x}^{5}}}{5}-\frac{{{x}^{7}}}{7}+.....0,\frac{\pi }{x}\le x\le \frac{\pi }{4}\]
Some basic formula,
\[\underset{x\to \infty }{\mathop{\lim }}\,{{\left\{ \text{f(x)} \right\}}^{g(x)}}=\underset{x\to \infty }{\mathop{\lim }}\,\,\,{{e}^{\left\{ \text{f(x)}-1 \right\}.g(x)}}\]
e.g. \[\underset{x\to \infty }{\mathop{\lim }}\,\frac{{{\left( 1+\frac{1}{x} \right)}^{x\to g(x)}}}{f(x)}=\frac{1}{x}=0\]
\[{{(1+0)}^{\infty }}={{1}^{\infty }}=\underset{x\to \infty }{\mathop{\lim }}\,\,\,e\left\{ f(x)-1) \right\}.g(x)=\underset{x\to \infty }{\mathop{\lim }}\,\,\,{{e}^{\left( 1+\frac{1}{x}-1 \right).x}}=\underset{x\to \infty }{\mathop{\lim }}\,\,\,{{e}^{x\times \frac{1}{x}}}={{e}^{1}}=e\]
\[\underset{n\to \infty }{\mathop{\lim }}\,\,\,n\frac{(\sqrt{{{n}^{2}}+4}-n}{\sqrt{{{n}^{2}}+4}+n}\times (\sqrt{{{n}^{2}}+4}+n)\] \[\left[ \because (a-b)(a+b)={{a}^{2}}-{{b}^{2}} \right]\]
\[\underset{n\to \infty }{\mathop{\lim }}\,\,\,n\frac{(\sqrt{{{n}^{2}}+4}-{{n}^{2}}}{\sqrt{{{n}^{2}}+4}+n}=\underset{x\to \infty }{\mathop{\lim }}\,\frac{4}{\sqrt{\frac{{{n}^{2}}+4}{{{n}^{2}}}}+\frac{n}{n}}=\underset{x\to \infty }{\mathop{\lim }}\,\frac{4}{\sqrt{1+\frac{4}{{{n}^{2}}}}+1}\]
Applying limit, \[n\to \infty ,\]we have
\[=\frac{4}{\sqrt{1+0}+1}=\frac{4}{2}=2.\left[ \because \frac{1}{\infty }=0 \right]\]
\[=\frac{4}{\sqrt{1+0}+1}=\frac{4}{2}=2\]
Sol: Let \[{{\sin }^{-1}}x=\theta \Rightarrow \sin \theta =x.\] Now, \[=\underset{x\to 0}{\mathop{\lim }}\,\frac{2.{{\sin }^{-1}}x}{3x}\] \[x\to 0\]
\[\sin \theta \to 0\]
\[\theta =0\]
\[\underset{x\to 0}{\mathop{\lim }}\,\frac{2\theta }{3.\sin \theta }\]
\[\underset{\sin \theta \to 0}{\mathop{\lim }}\,\frac{2}{3\left( \frac{\sin \theta }{\theta } \right)}=\underset{\theta \to 0}{\mathop{\lim }}\,\frac{\left( \frac{2}{3} \right)}{\frac{\sin \theta }{\theta }}=\frac{\frac{2}{3}}{1}=\left( \frac{2}{3} \right)\]
{we know that \[\cos \,\,3x=4{{\cos }^{3}}x-3\cos x\] \[\Rightarrow \] \[4{{\cos }^{3}}x=\cos 3x+3\cos x\]
and \[\sin 3x=3\sin x-4{{\sin }^{3}}x\}\]
\[=\underset{x\to \pi }{\mathop{\lim }}\,\left( \frac{1}{{{\tan }^{2}}x}+\frac{{{\cos }^{3}}x}{{{\tan }^{2}}x} \right)=\underset{x\to \pi }{\mathop{\lim }}\,\left( {{\cot }^{2}}x+\frac{{{\cos }^{3}}x}{\frac{{{\sin }^{2}}x}{{{\cos }^{2}}x}} \right)\]
\[\underset{x\to \pi }{\mathop{\lim }}\,\left( {{\cot }^{2}}x \right)+{{\cot }^{2}}x.{{\cos }^{3}}x\]
\[\underset{x\to \pi }{\mathop{\lim }}\,\left( \frac{{{1}^{3}}+{{\cos }^{3}}x}{{{\tan }^{2}}x} \right)\left[ \therefore {{a}^{3}}+{{b}^{3}}=(a+b)({{a}^{2}}-ab+{{b}^{2}}) \right]\]
\[\underset{x\to \pi }{\mathop{\lim }}\,\frac{(1+\cos x)(1-\cos x+{{\cos }^{2}}x}{({{\tan }^{2}}x)}=\underset{x\to \pi }{\mathop{\lim }}\,\frac{(1+\cos x)(1-\cos x+{{\cos }^{2}}x)}{\frac{{{\sin }^{2}}x}{{{\cos }^{2}}x}}\]
\[\underset{x\to \pi }{\mathop{\lim }}\,\frac{{{\cos }^{2}}x(1+\cos x)(1-\cos x+{{\cos }^{2}}x)}{({{1}^{2}}-{{\cos }^{2}}x)}\]
\[\underset{x\to \pi }{\mathop{\lim }}\,\frac{{{\cos }^{2}}x(1+\cos x)(1-\cos x+{{\cos }^{2}}x)}{(1-\cos x)(1-cosx)}=\frac{{{(-1)}^{2}}(1+1+1)}{1-(-1)}\frac{3}{2}\]
\[[\cos \,\,\pi =-1]\]
You need to login to perform this action.
You will be redirected in
3 sec